Upflow and downflow biological aerated filters (BAFs) for wastewater treatment - Mendoza-Espinosa, Leopoldo Guillermo (Cranfield University, 1999)
Investigations on two small pilot-scale biological aerated filters operating in upflow and downflow mode using identical media were undertaken in order to compare their performance for the removal of carbonaceous matter and ammonia, calibration of empirical models for suspended solids, soluble and total COD and their resistance to organic and hydraulic shock loadings. The initial existence of a plenum chamber under the media bed caused severe reduction in active volume in the downflow reactor. Elimination of the plenum chamber by means of the addition of media solved the problem and both reactors presented plug-flow conditions. Their performance for carbonaceous matter and ammonia removal was compared. With the exception of ammonia, the removal efficiencies for the parameters studied in both types of reactor were very similar. The downflow reactor achieved a greater removal of ammonia than the upflow BAF. Autrotrophic activity was located at the bottom of the reactor in the downflow column and at the top in the upflow unit. Had the running conditions been set identically for both columns, the difference in performance between the two reactors may have been due to the impact of the backwashing on the biological population, effectively washing-out the autotrophs. The verification of a simple empirical model for soluble COD removal for a different type of media than the previously reported was conducted. The new values for the media constant and the overall process constant of the system suggested that overall, the performance of the system was dictated by its media type/liquid flow characteristics. The constants from 4 empirical models were used to predict the removal of SS, sCOD and tCOD in a small BAF (0.07 m3 empty bed volume) and a large BAF (0.69 m3 empty bed volume). The model for soluble COD that included parameters such as gas and liquid velocity provided values closer to the actual observed values. The model for suspended solids and tCOD removal (based on a rapid gravity filters model) was efficient in predicting the overall removal rates of SS and tCOD in both reactors. When the models were used for scaling-up results, only the simplest model that did not include parameters such as gas and liquid velocity was effective. It was demonstrated that a small pilot-scale BAF was not capable of absorbing high peak organic shock loads when the organic loads were increased from a normal load of 1.2-1.4 kg sCOD m-3 d-1 to shock loads between 5.1- 7.3 kg sCOD m-3 d-1, based on empty bed volumes. Nevertheless, the effect on the biomass was limited as normal performance resumed very quickly. Increases in the hydraulic velocity from 0.7-1.0 m h' 1 to 1.5-2.9 m h" 1 had little affect on BAF performance in terms of soluble COD removal. Soluble COD effluent concentrations of <40 mg I-1 (-16 mg 1-1 BOD5) were detected thus, meeting most discharge consents in UK sewage works. The recovery of the reactor in both cases was fast, resuming normal performance within 60 min after the application of the shock load.